2013
DOI: 10.1001/2013.jamapediatrics.286
|View full text |Cite
|
Sign up to set email alerts
|

Recent National Trends in the Use of Adolescent Inpatient Bariatric Surgery

Abstract: Participants: Adolescents (defined herein as individuals aged 10-19 years) undergoing inpatient bariatric procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 53 publications
1
46
0
Order By: Relevance
“…A cross-sectional study looking at national surgical trends in obese adolescent patients found that RYGB was the most commonly performed weight reduction procedure for patients between 10 and 19 years of age in the United States, with RYGB comprising 67.6% of all interventions performed on this population. 63 Much like in adults, excellent results have been reported for adolescents undergoing RYGB with 35% reduction in weight seen at 1 year after surgery. 64 A meta-analysis of all bariatric surgery in pediatric patients reported decreases in BMI of 17.8 to 22.3 units.…”
Section: Mirenskymentioning
confidence: 95%
See 1 more Smart Citation
“…A cross-sectional study looking at national surgical trends in obese adolescent patients found that RYGB was the most commonly performed weight reduction procedure for patients between 10 and 19 years of age in the United States, with RYGB comprising 67.6% of all interventions performed on this population. 63 Much like in adults, excellent results have been reported for adolescents undergoing RYGB with 35% reduction in weight seen at 1 year after surgery. 64 A meta-analysis of all bariatric surgery in pediatric patients reported decreases in BMI of 17.8 to 22.3 units.…”
Section: Mirenskymentioning
confidence: 95%
“…Despite lack of FDA approval of the AGB for patients younger than 18 years, there had been a surge of AGBs implanted into adolescent patients in recent years with AGB insertions comprising almost one-third of all bariatric procedures performed in 2009 (approval for implantation was granted through investigational device exemption from the FDA). 63 Although initially thought to have an excellent safety profile with substantial loss of excess body weight (37%-63%) achieved during a 6-month to 7-year follow-up period, 70 reoperation rates of 8% to 10% for mechanical device failure, band slippage, band erosion, or band removal limited their use. 65 Although implantation of AGBs results in greater weight loss and improvement in quality of life indices and health status compared with nonoperative weight reduction approaches, there has been a drastic decline in the numbers of AGB devices implanted in pediatric patients in the United States today.…”
Section: Mirenskymentioning
confidence: 99%
“…41,42 Commonalities in these findings lie in the demographics, with a larger number of patients being female, privately insured, with an average age of 16 years, predominantly Caucasian, from high-income families. However, Medicaid use for these types of surgeries has increased from 7.7% in 2003 to 17.2% in 2009.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…However, Medicaid use for these types of surgeries has increased from 7.7% in 2003 to 17.2% in 2009. 41 Also, while some researchers found adolescent patients were more likely to receive bypass surgery, [41][42][43] one recent California study found gastric banding had increased, while bypass procedures had decreased. 44 Others report sleeve surgeries are becoming more readily selected 45 and have been performed on children as young as 7 years old.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…In addition to the exponential rise in obesity, a mounting body of evidence has shown a parallel increase in the prevalence of obesity-related co-morbid diseases (e.g., type 2 diabetes mellitus, insulin resistance, hypertension, hyperlipidemia, obstructive sleep apnea, liver disease) in the extremely obese adolescent population [3][4][5][6][7][8][9][10]. The combination of these observations, coupled with increasing evidence that obese children have a high propensity of becoming correspondingly obese adults [2], has recently resulted in a steady increase in the utilization of bariatric surgery in the pediatric age group [11,12].…”
mentioning
confidence: 99%